Leisure-time physical activity sustained since midlife and preservation of cognitive function: The Atherosclerosis Risk in Communities Study - Palta, Priya; Sharrett, A Richey; Deal, Jennifer A; Evenson, Kelly R; Gabriel, Kelley Pettee; Folsom, Aaron R; Gross, Alden L; Windham, B Gwen; Knopman, David; Mosley, Thomas H; Heiss, Gerardo (Alzheimer's & dementia, 2019)
We tested the hypotheses that higher levels of and persistence of midlife leisure-time physical activity (LTPA) are associated long-term with lower cognitive decline and less incident dementia. A total of 10,705 participants (mean age: 60 years) had LTPA (no, low, middle, or high) measured in 1987-1989 and 1993-1995. LTPA was assessed in relation to incident dementia and 14-year change in general cognitive performance. Over a median follow-up of 17.4 years, 1063 dementia cases were observed. Compared with no LTPA, high LTPA in midlife was associated with lower incidence of dementia (hazard ratio [95% confidence interval], 0.71 [0.61, 0.86]) and lower declines in general cognitive performance (-0.07 standard deviation difference [-0.12 to -0.04]). These associations were stronger when measured against persistence of midlife LTPA over 6 years. LTPA is a readily modifiable factor associated inversely with long-term dementia incidence and cognitive decline.